QIBLA JURISPRUDENCE: Deviation of Mosques’ Qibla in Pamekasan Madura - Jalil, Abdul; Hosen, Hosen (Islamuna: Jurnal Studi Islam, 2020)
The qibla direction of some mosques in Pamekasan encountered deviation after the recalibration was carried out, but only a few mosques changed their qibla direction according to the calculation of hisâb. This study discusses three issues, namely: Society’s understanding of the direction of the mosque’s qibla, their responses to deviations from the direction of the mosque’s qibla, and the implications of the deviation of the mosque’s qibla on the validity of prayer in the perspective of falak science and Islamic law. With a qualitative-descriptive approach based on semi-structured interviews and non-participant observation, this study reveals that some congregants still regard the west as the direction of the qibla and do not understand the provisions of having to face the qibla during prayers; there are three axes of the congregation’s response to the deviation of the direction of the mosque’s qibla, namely serious, ordinary, and indifferent; and mosques that experience deviation according to astronomy are not following the provisions facing the qibla, so they must be repaired so that the prayers are perfect according to the provisions of Islamic law.[Sebagian arah kiblat masjid di Pamekasan mengalami deviasi setelah rekalibrasi dilakukan, tetapi hanya sedikit masjid yang mengubah arah kiblatnya sesuai perhitungan ilmu hisab. Artikel ini mendiskusikan tiga persoalan, yaitu: pemahaman masyarakat tentang arah kiblat masjid, respons masyarakat terhadap penyimpangan arah kiblat masjidnya, dan implikasi deviasi arah kiblat masjid terhadap keabsahan salat dalam perspektif ilmu falak dan hukum Islam. Dengan pendekatan kualitatif-deskriptif berdasarkan wawancara semi terstruktur dan observasi nonpartisipan, artikel ini mengungkap bahwa sebagian jemaah masih menganggap arah barat sebagai arah kiblat dan tidak memahami ketentuan harus hadap kiblat saat salat; ada tiga poros respons jemaah terhadap deviasi arah kiblat masjidnya, yaitu serius, biasa, dan cuek; dan masjid yang mengalami deviasi menurut ilmu falak tidak sesuai dengan ketentuan menghadap kiblat, sehingga harus diperbaiki agar salat menjadi sempurna sesuai ketentuan hukum Islam]